Repeatability of quantitative MRI in patients with rheumatoid arthritis. Issue 3 (August 2022) - Bertham, D.P.; Tan, A.L.; Booth, A.; Paton, L.; Emery, P.; Biglands, J.; Farrow, M.
Abstract: Introduction: Rheumatoid arthritis (RA) affects 1% of the population and is principally associated with joint inflammation. It is suggested however that muscle involvement may be one of the earliest clinical features of RA. It is therefore important that techniques exist to accurately assess muscle health in those with RA to enable successful treatment. This study assesses the inter-rater and intra-rater repeatability of Diffusion Tensor MRI (DTI), 2-Point Dixon fat fraction, and T2 relaxation of the thigh muscle in patients with RA using manual regions of interest (ROI). Methods: Nineteen patients (10/19 males; mean age 59; range 18–85) diagnosed with RA had an MRI scan of their hamstrings and quadriceps muscles to obtain fat fraction (FF), mean diffusivity (MD), fractional anisotropy (FA), and T2 quantitative measurements. Two raters DB & MF independently contoured ROIs for each patient. DB repeated the ROI for the same 19 patients after a 6-month hiatus to assess intra-rater repeatability. Inter-rater and intra-rater repeatability for the ROI measurements were compared using Inter Class Correlation (ICC) and Bland–Altman plots. Results: There was excellent agreement for both inter-rater and intra-rater repeatability. ICC results ranged from 0.900 to 0.998 (P < 0.001), and intra-rater ICC results ranged from 0.977 to 0.999 (P < 0.001). Bland–Altman plots also showed excellent agreement. Conclusions: ICC measurements and Bland–Altman plots showed excellent repeatability and agreement with no statistically significant differences when assessing the inter-rater and intra-rater repeatability of FF, MD, FA, and T2 relaxation of the thigh muscle using manual regions of interest in patients with RA. Implications for practice: Manual ROI drawing does not introduce significant errors obtaining FF, MD, FA, and T2 MRI measurements in an RA population.